Alimentación y cultura en España - Fernández Álvarez, Óscar (Estudios humanísticos. Geografía, historia y arte, 1996)
Moreover an evident answer to lively needed, culinary practice is alive expression of a whole hipe cultural aspects, so material or spiritual condition. Those have remained in the feeling of the people, and in many instances, changed, diversified, or even, dissapeared or faded away, according to temporal and spatial coordinates. A strong socio-economic and politic-religious transcript close to a diversity of landscapes, contributed to give distinction to alimentary customs of a country like Spain. Through the spanish case, we'll show how the gastronomy practice is undetacheble of daily occupation in all cultures, and so to transmit a whole of notions that make possible, each one's own situation, in the consideration that food constitutes one more aspect of cultural heritage of the people.